Effects of a new experimental training program on VO2max and running performance - Sporis, G.; Ruzic, L.; Leko, G. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: By testing the V.O2max and running performance in soccer players, the purpose of the study was to determine whether an experimental conditioning program would elicit better effects than the widely used traditional program, especially across longer distances. Methods: Laboratory measurements of maximal oxygen consumption and maximal heart rate were performed on 48 soccer players (U19) from two first league soccer teams (Experimental team, n=24; Control team n=24). Exercise intensities were calculated from heart rate maximum. Detailed training programs for both the experimental and control groups were designed for the 13-week period. The main intervention was performed in the conditioning phase where the control group performed traditional conditioning (straight-line running, with stretching exercises in the break) and the experimental group underwent a conditioning training program on designed polygon, very much akin to a real game situation; sprint-runs with or without the ball and rapid changes in direction. During the 20, 40 or 60m sprint-run the players had to perform specific ball drills depending on marked polygon station. Running performance at 60, 100, 200, 400, 800, 1200, 2 400 m distances and V.O2max were tested in the initial, transitory (week 6) and final trials. Results: Significant improvement in 200, 400, 800, 1200, 2 400 m running performance and VO2max (P<0.01), occurred in the experimental group after only 6 weeks of program and increased more after 13 weeks. Some non-significant improvement was observed in the control group at the time of the transitory trial. However, in this group the gained improvements quickly disappeared after the beginning of the competitive season as recorded at the final trial. Discriminant analysis revealed that the groups differed the most in the 200 m variable. Conclusion: The new experimental program is better suited for the enhancement of V.O2max and running performance in soccer players and the gained improvement lasted well into the competition season.